Charophytes: Evolutionary Giants and Emerging Model Organisms - Domozych, David; Popper, Zoë A.; Sorensen, Iben (Frontiers in Plant Science, 2016)
Charophytes are the group of green algae whose ancestral lineage gave rise to land plants in what resulted in a profoundly transformative event in the natural history of the planet. Extant charophytes exhibit many features that are similar to those found in land plants and their relatively simple phenotypes make them efficacious organisms for the study of many fundamental biological phenomena. Several taxa including Micrasterias, Penium, Chara and Coleochaete are valuable model organisms for the study of cell biology, development, physiology and ecology of plants. New and rapidly expanding molecular studies are increasing the use of charophytes that in turn, will dramatically enhance our understanding of the evolution of plants and the adaptations that allowed for survival on land. The Frontiers in Plant Science series on “Charophytes” provides an assortment of new research reports and reviews on charophytes and their emerging significance as model plants.